Wilhelm von Waldeyer-Hartz—A Great Forefather: His Contributions to Anatomy with Particular Attention to “His” Fascia - Scheuerlein, Hubert; Henschke, Frank; Köckerling, Ferdinand (Frontiers in Surgery, 2017)
Wilhelm Waldeyer was, at his time, one of the most well-known authors in the field of Anatomy, Pathology and Embryology. He held various distinguished academic positions. He was Professor of (Pathological) Anatomy in Breslau, Strasbourg and Berlin. He remained in Berlin for the unusually long period of 33.5 years, as Full Professor for Anatomy and Director of the Anatomical Institute. His great talent as a teacher ensured that his lectures were always filled to the brim. Between 1862 and 1920, he published 270 works, including classics such as „Das Becken“ (The Pelvis). The portrayal of this most important area is counted as one of the most complete which has ever been accomplished in the field of topographic anatomy, it includes the description of the Fascia of Waldeyer. He also coined the phrases „chromosome“ and „neuron“ with their anatomical-morphological concepts. Already during his lifetime, his teaching ability significantly preceded the research capacity. It would, however, be false to overshadow Waldeyer’s merits as a researcher. His main scientific merit is in his excellent summarising interpretations of current questions of anatomy and evolution, which particularly shows his simultaneous gift as a researcher and a teacher.